Optical lithography : here is why - Lin, Burn Jeng, 1942- (SPIE monograph ;, 2010)
This book is aimed at new and experienced engineers, technology managers, and senior technicians who want to enrich their understanding of the image formation physics of a lithographic system. Readers will gain knowledge of the basic equations and constants that drive optical lithography, learn the basics of exposure systems and image formation, and come away with a full understanding of system components, processing, and optimization. Readers will also get a primer on the outlook of optical lithography and the many next-generation technologies that may greatly enhance semiconductor manufacturing in the near future.